The apolipoprotein B and apolipoprotein A-I Ratio serves as a strong prognostic factor for the overall survival of patients with colorectal cancer - Pan, Yangxun; Ye, Zhiwei; Ling, Yihong; Kong, Lingheng; Wang, Chenwei; Chen, Gong; Wan, Desen; Chen, Minshan; Hu, Dandan (Frontiers in Oncology, 2023)
Background: The lipid metabolism status of patients with colorectal cancer (CRC) has not been understood comprehensively. The present study investigated the characteristics of lipid metabolism parameters in CRC patients with or without metastases and identified the independent prognostic factors of long-term outcomes. Methods: The clinicopathological data of 231 CRC patients along with 259 formalin-fixed paraffin-embedded samples with or without liver or lung metastasis were retrieved and stained for apolipoprotein B (apoB) via IHC in our center. The correlation analysis and multivariable analysis based on overall survival (OS) was analyzed. Results: In the multivariable analysis, apolipoprotein A-I (apoA1), apoB and apolipoprotein B and apolipoprotein A-I (apoB/A) ratio, were identified as independent prognostic factors for OS. Moreover, the apoB/A ratio showed a significantly negative association with OS time (R=-0.187, P=0.004). CRC patients with low apoB/A ratio had better 1-, 3- and 5-year OS rates than those who had high apoB/A ratio (87.1%, 54.3%, and 37.1% vs. 92.5%, 72.0%, and 59.5%, respectively, P=0.001). On histological level, similar expression intensity of apoB between primary CRC and liver metastases indicated better prognostic outcomes than those with different expression levels (100%, 83.3%, and 77.8% vs. 100%, 66.7%, and 33.3%, respectively; P=0.033). Higher level of apoB in the primary CRC interprets into increased incidence of liver metastases. However, the apoB expression levels in the CRC tumor were not parallel to the circulating lipid metabolism parameters. Conclusions: The apoB/A ratio was a strong independent prognostic factor for predicting the long-term OS of CRC patients. Moreover, the IHC of the primary CRC and metastatic lesions verified the metastatic potential of apoB through a different angle. Lipid metabolism status for cancer progression reported in the present study possesses potentially prognostic value, but bench-scale studies are needed for their future clinical application.